Study on Hunting Park in Yugoslavia - Sumarjono Soedargo; Warsito . (Media Konservasi, 1990)
A collaboration between the Government of Indonesia and Yugoslavia has been carried out in the framework of hunting tourism in Indonesia. This collaboration has begun since 1987, in which a joint field survey to some Hunting Reserves in Indonesia, namely Masigit-Kareumbi. Movo Island, Bukit Soeharto Provincial Forest and Rempang Island, was carried out by a team from the Directorate General of Nature Conservation and Forest Protection and the Government of Yugoslavia.For further development of hunting tourism, the Directorate General of Nature Conservation and Forest Protection had sent Ir Sumarjono Soedargo and Ir Warsito to Yugoslavia in April - June 1989. This program was aimed to study the hunting reserves management and hunting activities, with special emphasis on game production and breeding, in Yugoslavia.Basically, the key to the succesful hunting reserves management in Yugoslavia is the breeding program. This is also supported by the success of hunting activities management in which 90% of the hunters came from other countries, for instance Germany, Itali, Austria, Netherlands, Swiss and France. This paper describes the results of the visit to several Hunting Districts in Yugoslavia.